Enhancing Knowledge and Compliance in Anemia Treatment Through a WhatsApp Group at SMPN 1 Karangrejo, Magetan, Indonesia - Devi Kristyani; Astin Nur Hanifah; Heru Santoso Wahito Nugroho; Suparji Suparji (Knowledge Dynamics, 2024)
Background: The prevalence of anemia in adolescents in East Java in 2018 was 50-60%. Anemia can be caused by various factors, including iron deficiency, vitamin B12 deficiency, folate deficiency, infectious diseases, congenital factors, and bleeding. The Indonesian government has intensified the anemia prevention and control program in adolescent girls and women of childbearing age by prioritizing the provision of iron tablets, one tablet per week, to reduce the prevalence of anemia in this group by 2025. In the millennial era, many adolescents and the community use WhatsApp as a means of communication. For promotional media, researchers chose WhatsApp media and it is hoped that health promotion efforts and the movement to drink TTD (iron supplement) together through WhatsApp media can increase the knowledge and compliance of rheumatology specialist doctors in consuming TTD. Method: This study is included in pre-experimental research using one group pretest and posttest by conducting a pretest before being given treatment and then conducting a posttest after being given treatment. The sample in this study was adolescent girls at Junior High School 1 Karangrejo Magetan Indonesia as many as 92 respondents. The independent variables are health promotion and the movement to drink TTD together through Whatsapp Group. The deeper variable in this study is knowledge about anemia. Results: The results showed a significant difference between knowledge about anemia and compliance in taking iron tablets before and after the intervention, with a p-value of 0.000 (≤ 0.05). This shows that health promotion and the movement to drink iron tablets together through WhatsApp Group are effective in increasing knowledge and compliance. Conclusion: Health promotion and the movement to drink blood tablets together through WhatsApp Group are effective in increasing knowledge and compliance and there is an increase in knowledge and compliance scores after health promotion.